Federal Republic of Yugoslavia : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This report is an assessment of the status of the Federal Republic of Yugoslavia'sfinancial accountability at June 2002. This first CFAA for the FRY focuses on the most critical issues in the near-to-medium term. In this context, the CFAA concentrates on public sector accountability and on fiduciary arrangements for Bank-financed projects, with a limited review of private sector accounting and auditing arrangements that focuses on those issues that might affect the fiduciary safeguards and arrangements. The report is arranged as follows: Section 2 examines punlic sector budget management. Section 3 focuses on public sector payments, cash management, and treasury. Section 4 assesses public sector accounting and reporting. Section 5 describes public sector financial controls, and internal and external audit capabilities. Section 6 scrutinizes banking, accounting, and fiduciary considerations in the financial and private sectors; and elaborates fiduciary risk assessment and management.